Cranial Ultrasound Screening of Low Birth Weight Infants - Immanuel Mustadjab (Paediatrica Indonesiana, 1996)
Cranial ultrasound examination was performed on 9 L low birth weight inÂfants to determine the occurence of cerebral hemorrhage with or without ventricu- lomegaly. In very low birth weight infants cerebral hemorrhage was found in 35%, while the hemorrhage plus ventriculomegaly was found in 18% of the infants. In all low birth weight infants cerebral hemorrhage was found in 17%, while hemorrhage plus ventricuÂlomegaly was found in 8% of the infants. In dysmature infants, cerebral hemorrhage wasfound in 10%. Severe asphyxia was associated with hemorrhage or hemorrhage plus ventriculomegaly, where the incidence was 45% and 17%, respectively.